2017
DOI: 10.47611/jsr.v6i2.392
|View full text |Cite
|
Sign up to set email alerts
|

Emphasis of University Supervisor Feedback to Teacher Candidates

Abstract: The purpose of this study is to analyze the emphasis of the feedback that university supervisors give to teacher candidates.  Specifically, we seek to understand the relation of praise versus area of growth and how the emphasis relates to the focus of feedback. Data included coded observation reports from eight university supervisors. The three main findings were: praise feedback had a significantly higher amount than area of growth feedback, feedback emphasized certain skills over others, and a significant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 12 publications
2
11
1
Order By: Relevance
“…The text-based group suggested that they were not as confident they received the needed input to improve their performance. However, results differed from prior studies by Tripp and Rich ( 2012 ) and Vertemara and Flushman ( 2017 ) which previously found participants were significantly less likely to remember the feedback at a later time. Effective feedback should provoke the recipient to evaluate their teaching practice with the aim of continuous improvement (Sailors and Price 2015 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The text-based group suggested that they were not as confident they received the needed input to improve their performance. However, results differed from prior studies by Tripp and Rich ( 2012 ) and Vertemara and Flushman ( 2017 ) which previously found participants were significantly less likely to remember the feedback at a later time. Effective feedback should provoke the recipient to evaluate their teaching practice with the aim of continuous improvement (Sailors and Price 2015 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Instructors, cooperative teachers, and supervisors play significant roles and offer unique perspectives in the development of preservice teachers. Participants in prior research stated they trusted a supervisor's opinion more than their own (Baecher et al 2018 ; Vertemara and Flushman 2017 ). However, the use of video as a feedback tool can impact the experience novice teachers receive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the major roles of practicum supervisors is to give critical and constructive feedback to STs to improve their lessons and teaching skills, including lesson planning, management, and assessment (Vertemara & Flushman, 2017). Peer feedback is usually not comprehensive to help STs improve their teaching skills (Astrid, et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that preservice teachers (PTs) would develop and integrate their knowledge, skills, and attitudes gained in theoretical courses in the teacher training programs. The practicum field experience in teacher education is one of the major steps and influential factors in the preparation of preservice teachers (Badger, 2012;Steadman & Brown, 2011;Vertemara & Flushman, 2017). It gives PTs an opportunity to apply the theoretical concepts learned in the university classroom to the primary/secondary school classroom (Eck & Ramsey, 2019) and establish collaborative contexts for interactions among preservice teachers (PTs), cooperative teachers (CTs) and university supervisors (USs) who are putting into practice the ways of thinking, doing, and speaking advocated by reform documents (Van Zee et al, 2003).…”
mentioning
confidence: 99%
“…Because mentors are especially important in helping PTs to reflect upon their teaching and in providing access to a range of knowledge areas to assist PTs in their professional development, mentoring has come to be viewed as a means of reforming science teaching (Clarke et al, 2014;Koballa & Bradbury, 2012;Sandvik et al, 2019). USs who serve as mentors share the responsibility of guiding PTs with CTs about reformbased science teaching and creating a connection between the practice schools and the university by visiting the schools (Vertemara & Flushman, 2017). They are expected to support PTs' implementation of theories learned in coursework with appropriate feedback to provide and enrich learning and skill development opportunities in the final stage of teacher preparation (Fernandez & Erbilgin, 2009;Hudson, 2014;Steadman & Brown, 2011).…”
mentioning
confidence: 99%